Fiscal Decentralisation and Inequality in Indonesia - Digdowiseiso, Kumba; Sugiyanto, Eko; Setiawan, Heru Dian (Economy of Regions, 2020)
The study examined the effect of fiscal decentralisation on both vertical and horizontal inequality in 32 provinces of Indonesia in the period from 2005 to 2014 using several fixed effects (FE) estimations. Moreover, we assessed the mediating role of institutional quality in explaining the nexus between fiscal decentralisation and inequality. To complement the econometrics results, we conducted several semi-structured interviews (SSIs) based on expert judgement and focus group discussions (FGDs) among relevant stakeholders. This analysis focussed on the intergovernmental transfer policy designed and implemented at the sub-national government level. Such qualitative analysis started in the last week of March 2019 and ended in the first week of July 2019. The quantitative findings showed that there was a robust, positive, and significant relationship between fiscal decentralisation and vertical inequality when democracy was taken into account. Meanwhile, fiscal decentralisation was negatively correlated with horizontal inequality when the estimation included social capital. In addition, fiscal decentralisation appears to have a marginal impact on horizontal inequality when both democracy and the crime rate are considered in the full sample analysis. However, when we excluded provinces located in Java Island, the impact of fiscal decentralisation on horizontal inequality became clear. Regarding the qualitative aspect, the fieldwork results were consistent with the quantitative findings.